Factors Promoting Development of Fibrosis in Crohn’s Disease - Rogler, Gerhard; Hausmann, Martin (Frontiers in Medicine, 2017)
The concepts on the pathophysiology of intestinal fibrosis in Crohn’s disease (CD) have changed in recent years. Some years ago fibrosis was regarded to be a consequence of long standing inflammation with subsequent destruction of the gut wall matrix followed by scar formation and collagen deposition. Fibrosis in CD patients appeared to be an irreversible process that could hardly be influenced. Therefore, the main target in CD therapy was to control inflammation in order to avoid fibrosis development. Many of these assumption seem to be only partially true. Inflammation may be a necessary pre-requisite for the initiation of fibrosis. However, when the pathophysiologic processes that lead to fibrosis in CD patients have been initiated fibrosis development may be independent of inflammation and may continue even when inflammation is under good medical control. Fibrosis in CD also may be reversible. After strictureplasty local collagen deposits decrease or even disappear. With new animal models for intestinal fibrosis on the horizon, we need to spend more efforts on understanding the factors influencing fibrosis in CD patients to finally find specific therapies. In this context it will be as important to find markers and quantitative imaging tools to have reliable endpoints for clinical trials in fibrosing CD.